Mutually Exclusive Cellular Uptake of Combinatorial Supramolecular Copolymers - van Dun, Sam (Chemistry, 2018)
The cellular uptake of self‐assembled biological and synthetic matter results from their multicomponent properties. However, the interplay of the building block composition of self‐assembled materials and uptake mechanisms urgently requires addressing. It is shown here that supramolecular polymers that self‐assemble in aqueous media, are a modular and controllable platform to modulate cellular delivery by the introduction of small ligands or cationic moieties, with concomitantly different cellular uptake kinetics and valence dependence. A library of supramolecular copolymers revealed stringent mutually exclusive uptake behavior in which either of the uptake pathways dominated, with sharp compositional transition. Supramolecular biomaterial engineering thus provides for adaptive platforms with great potential for efficient tuning of multivalent and multicomponent systems interfacing with biological matter.